PERUBAHAN UNSUR RITUS KEAGAMAAN MASYARAKAT BALI AGA DI DESA BAYUNG GEDE, KECAMATAN KINTAMANI, BANGLI, BALI - Ni Wayan, Linda Oktari Dewi (Humanis; Volume 12. No.3. September 2015, 2015)
Majapahit invasion hundreds of years ago has led to polarization of the Balinese people, namely the people of Bali Aga and Bali Majapahit. Both communities are mutually change. It is a natural thing for society and culture for being dynamic and constantly changing. However, in these changes are interesting facts to be studied, namely a change in religious rites related elements of religion in the public system of Bali Aga at Bayung Gede, whereas Koentjaraningrat (1986: 204) describes the seven elements of universal culture, religion systems is the most difficult to change. This phenomenon has implications for the element in the religious rites at Bayung Gede related changes in religious leadership and community treatment in the tradition of hanging placenta , so it is necessary to study about why did the element in the religious rites change ? And how are the implications of culture change in that society of Bayung Gede ? Based on those statements , in this research use descriptive qualitative as a basic methodology. The theories are concern with culture change and culture adaptation, and based on concepts are change of the religious rites and society of Bali Aga in Bayung Gede. The result of this research are study about exogamy tradition, religion education, dynamic of society conviction, and refunctionalisation of religious leadership as the essential factors of culture change. The implications are increased the assignment of society, role division of religious leadership, and symbolic diversity in religious rites .
Keywords: change, culture, rites